TEACHING LISTENING SKILL TO FIFTH GRADE STUDENTS OF SD NEGERI GEUMPANG KABUPATEN PIDIE BY WATCHING YOUTUBE CHANNEL PRACTICAL PSYCHOLOGY - Ayu Azizah; Siti Mayang Sari; Akmaluddin; Rita Novita (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The goal of this study is to determine whether students in SD Negeri Geumpang's fifth grade who receive listening instruction via YouTube Channel Practical Psychology do better than those who receive listening instruction without it. In the case of the experiment research method, quantitative research is used to conduct this study. The research's design is a pre-experiment with one group that underwent pre- and posttesting. One class is used in this arrangement, and pre- and post-tests are administered before and after treatment. The purpose of this treatment is to test the effects of a certain treatment. The kids of SD Negeri Geumpang's fifth grade during the academic year 2022/2023 make up the study's population. 28 students make up the entire student body, which is divided into one class. Only 28 pupils in the fifth grade are used in this study's sample because there are so few of them. N-Gain Score was used to analyze the data that was obtained. The study's findings indicate that fifth-grade students at SD Negeri Geumpang perform better when listening skills are taught via YouTube Channel Practical Psychology than when listening skills are taught without it. This is supported by It is demonstrated by the N-Gain score calculation result, which is 0.58. Utilizing the Practical Psychology YouTube channel to teach listening skills is not sufficient or effective enough.